Всем сестрам...: [рассказы] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2012)
Экземпляры: ф.18 (ретро) / Инвентарный номер: 49117 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6